REFORMASI KEBIJAKAN PERBANKAN ISLAM DI INDONESIA - Muslimin Muslimin (State Islamic University North Sumatra, 2008)
Abstract: Reformation of Syari’ah Banking Policy in Indonesia. The existence of Islamic banking in Indonesia gains recognition with the introduction of the government regulation of 1992 concerning the foundation of Islamic banking. Six years later the government introduced Law No. 10/1998 on reform of the banking system. As a result, reform of banking system, (conventional bankis possible to provide branch office based on syari’ah principles); reform of Islamic banking programs as well as monetary system; and reforms in accelerating of the Islamic banking development. This essay is an attempt to analyze the changes and implication brought with this regulation for the development of Islamic banking.Kata Kunci: politik, hukum, perbankan syariah